2020
DOI: 10.1039/d0nj00406e
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent synthesis of diphenyl-1,3-thiazole-barbituric acid hybrids and their fluorescence property studies

Abstract: A series of novel diphenyl-1,3-thiazole linked barbituric acid hybrids (4) were prepared by two catalyst-free methods from readily available starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…5-(2,4-Diphenylthiazol-5-yl)-1,3-dimethylpyrimidine-2,4,6-(1H,3H,5H)-trione (10a). 34 The product was purified by crystallization in ethyl acetate. Yield 163 mg (83%); white solid; 1 (m, 3H), 7.47 (t, J = 10.0 Hz, 2H), 7.36 (t, J = 10.0 Hz, 1H), 3.18 (s, 6H).…”
Section: -(24-diphenylthiazol-5-yl)-5-methyl-1-(oxiran-2-ylmethyl)-2p...mentioning
confidence: 99%
See 1 more Smart Citation
“…5-(2,4-Diphenylthiazol-5-yl)-1,3-dimethylpyrimidine-2,4,6-(1H,3H,5H)-trione (10a). 34 The product was purified by crystallization in ethyl acetate. Yield 163 mg (83%); white solid; 1 (m, 3H), 7.47 (t, J = 10.0 Hz, 2H), 7.36 (t, J = 10.0 Hz, 1H), 3.18 (s, 6H).…”
Section: -(24-diphenylthiazol-5-yl)-5-methyl-1-(oxiran-2-ylmethyl)-2p...mentioning
confidence: 99%
“…5-(2,4-Diphenylthiazol-5-yl)-1,3-dimethylpyrimidine-2,4,6-(1H,3H,5H)-trione (10a). 34 The product was purified by crystallization in ethyl acetate. Yield 163 mg (83%); white solid; 1 H NMR (500 MHz, DMSO-d 6 ): δ 7.90 (d, J = 5.0 Hz, 2H), 7.80 (d, J = 5.0 Hz, 2H), 7.49 (t, J = 10.0 Hz, 2H), 7.43 (t, J = 10.0 Hz, 1H), 7.29 (t, J = 10.0 Hz, 2H), 7.19 (t, J = 10.0 Hz, 1H), 3.08 (s, 6H).…”
Section: -(4-chlorophenyl)-3-methyl-4-(2-phenyl-4-(p-tolyl)-1h-imidaz...mentioning
confidence: 99%
“…Mahata et al reported the synthesis of a series of diphenyl-1,3thiazoles linked with barbituric acid moiety by a simple, catalystfree mechanochemical method. 37 The hand-grinding of arylglyoxal (25), barbituric acid (26), and aryl thioamides (27) in a mortar, assisted by a small amount of water for LAG, provided the corresponding trisubstituted thiazole−barbituric acid (28) within 30 min in high yields (Scheme 7). The molecules displayed fluorescence properties with emission maxima ranging from 495−562 nm.…”
Section: Mechanosynthesis Of Miscellaneous Dyesmentioning
confidence: 99%
“…40 At first, rhodamine 6G (35) was ground with hydrazine hydrate in an agate mortar with a pestle for 10 min to obtain rhodamine 6G hydrazide (36) in 95% yield. It was further condensed with different aromatic aldehydes (37) by mortar and pestle grinding to afford the chemosensors (38) in excellent yields (Figure 2A). Each of them displayed selective recognition ability toward Cu 2+ ions in a "turn-on" manner by complex formation (Figure 2B).…”
Section: Mechanochemical Synthesis and Modification Of Fluorophores F...mentioning
confidence: 99%
“…In addition, combination with other disciplines such as photochemistry, electrochemistry, or in situ spectros­copy paved the way for new creative synthetic strategies. Numerous scientific communities, including inorganic, main group, coordination, organometallic, catalytic, pharmaceutical, macromolecular, supramolecular, and organic chemistry, became involved. ,, In the latter, multicomponent reactions for preparing sulfur-containing and nitrogen-containing heterocycles have greatly benefitted from mechanochemical applications …”
mentioning
confidence: 99%